Update Cheryomushki: perspectives for future housing - Engel, Barbara (project baikal, 2021)
The shortage of residential space in many urban areas and the question about how this can be alleviated leads to the existing large residential housing estates, which are of great significance when it comes to providing living space for broad sections of the population in the future. Large housing estates potentially have a valuable role to play in providing housing – the dwellings there are highly adaptable, making them suitable for designing a living environment with few barriers, and they also have a high proportion of open spaces. In order to transform prefabricated dwelling areas into attractive neighborhoods and wanted housing not only the existing urban fabric have to be renovated and new types of dwelling integreated but as well the open spaces shall be improved. .